X chromosome inactivation in human cells - Migeon, Barbara (Henry Stewart Talks, 2010)
Advantage of human model systems, Silencing human inactive Xes, Species differences in underlying mechanisms, specifically, in regard to parental imprinting and TSIX, Choosing the single active human X and the role of autosomal transfactors in the process
Reviewed at 2016/06/29